Biostimulant Effects of Plant Extracts on Seed Germination and Storage Stability - Jyoti; Harish Kumar (Archives of Current Research International, 2025)
Biostimulants derived from plant extracts have gained attention for their potential to enhance seed germination and improve storage stability. This study investigates the effects of various plant extracts (e.g., moringa, neem, aloe vera) on seed germination rates and storage longevity in selected crops. Experiments were conducted under controlled conditions, evaluating germination percentage, seedling vigor, and post-storage viability. Results indicate that certain plant extracts significantly improve germination rates and seed shelf life compared to untreated controls. The findings suggest that plant-based biostimulants could serve as eco-friendly alternatives to synthetic treatments in agriculture.